2020
DOI: 10.1155/2020/8860968
|View full text |Cite
|
Sign up to set email alerts
|

EA Ameliorated Depressive Behaviors in CUMS Rats and Was Related to Its Suppressing Autophagy in the Hippocampus

Abstract: Autophagy is confirmed to be involved in the onset and development of depression, and some antidepressants took effect by influencing the autophagic process. Electroacupuncture (EA), as a common complementary treatment for depression, may share the mechanism of influencing autophagy in the hippocampus like antidepressants. To investigate that, sixty Sprague-Dawley rats firstly went through chronic unpredictable mild stress (CUMS) model establishment, and 15 rats were assigned to a control group. After modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
3
27
0
1
Order By: Relevance
“…In particular, we found that the mTOR, which is involved in the regulation of autophagy and inflammation signaling pathway ( Chu et al, 2020 ; Yao et al, 2020 ) was enriched. Further study found that mTOR signaling pathway is inhibited in CUMS rat model, which is in agreement with the results reported previously ( Zhang et al, 2020 ; Zhuo et al, 2020 ). SQSTM1, which was also upregulated in CUMS rat model, is associated with autophagy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, we found that the mTOR, which is involved in the regulation of autophagy and inflammation signaling pathway ( Chu et al, 2020 ; Yao et al, 2020 ) was enriched. Further study found that mTOR signaling pathway is inhibited in CUMS rat model, which is in agreement with the results reported previously ( Zhang et al, 2020 ; Zhuo et al, 2020 ). SQSTM1, which was also upregulated in CUMS rat model, is associated with autophagy.…”
Section: Discussionsupporting
confidence: 93%
“…SQSTM1, which was also upregulated in CUMS rat model, is associated with autophagy. Moreover, the expression of LC3II was increased in the CUMS rat model, which is consistent with the results reported previously ( Zhang et al, 2020 ). Therefore, it is reasonable to speculate that SQSTM1 could play a crucial role through regulated autophagy in MDD.…”
Section: Discussionsupporting
confidence: 93%
“…The SPT is also commonly used to analyze depressive‐like behavior since this test provides information relating to anhedonia, one of the main depressive‐like symptoms (Goñi‐Balentziaga et al., 2018 ). As a widely applied animal model for depression, the CUMS model presents many core depressive behaviors, including helplessness, anhedonia, and reduced locomotor activity (Z. Zhang et al., 2020 ). In particular, K252a, a TrkB antagonist was injected into mice exposed to CUMS and completely blocked the BDNF‐TrkB signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…2020; Zhang et al . 2020;), the CUMS modelling method was modified on the basis of Willner et al . to replicate the depression model (Willner et al .…”
Section: Methodsmentioning
confidence: 99%